Refractory invasive aspergillosis controlled with posaconazole and pulmonary surgery in a patient with chronic granulomatous disease: case report - KEPENEKLİ KADAYİFCİ, EDA; ERMERAK, NEZİH ONUR (BIOMED CENTRAL LTD, 2014)
Invasive aspergillosis is an important cause of morbidity and mortality in immunocompromised patients. Among primary immunodefiencies, chronic granulomatous disease (CGD) has the highest prevalence of invasive fungal diseases. Voriconazole is recommended for the primary treatment of invasive aspergillosis in most patients. In patients whose aspergillosis is refractory to voriconazole, therapeutic options include changing class of antifungal, for example using an amphotericin B formulation, an echinocandin, combination therapy, or further use of azoles. Posaconazole is a triazole derivative which is effective in Aspergillosis prophylaxis and treatment. Rarely, surgical therapy may be needed in some patients. Lesions those are contiguous with the great vessels or the pericardium, single cavitary lesion that cause hemoptysis, lesions invading the chest wall, aspergillosis that involves the skin and the bone are the indications for surgical therapy. Chronic granulomatous disease (CGD) is an inherited immundeficiency caused by defects in the phagocyte nicotinamide adenine dinucleotidephosphate (NADPH) oxidase complex which is mainstay of killing microorganisms. CGD is characterized by recurrent life-threatening bacterial and fungal infections and by abnormally exuberant inflammatory responses leading to granuloma formation, such as granulomatous enteritis, genitourinary obstruction, and wound dehiscence. The diagnosis is made by neutrophil function testing and the genotyping. Herein, we present a case with CGD who had invasive pulmonary aspergillosis refractory to voriconazole and liposomal amphotericine B combination therapy that was controlled with posaconazole treatment and pulmonary surgery.
Keywords: Chronic granulomatous disease; Invasive pulmonary aspergillosis; Posaconazole; HEMATOPOIETIC ALLOGRAFT; CLINICAL-FEATURES; FUNGAL-INFECTION; THERAPY; ITRACONAZOLE; PATHOGENESIS; MULTICENTER; MANAGEMENT